2021
DOI: 10.1108/jeim-08-2020-0331
|View full text |Cite
|
Sign up to set email alerts
|

The impact of enterprise social media use on employee performance: a grounded theory approach

Abstract: PurposeEnterprise social media (ESM) are frequently used in enterprises for daily operation. Although many researchers have attempted to understand the antecedents and consequences of ESM use, the integrated model, boundary conditions and mechanism of the impact of ESM use on performance are still unclear. This study fill this research gap by adopting a grounded theory approach to study how ESM use affects employee performance.Design/methodology/approachChoosing representative cases, the authors collected inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
3

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 84 publications
0
25
0
3
Order By: Relevance
“…From an analysis of the relevant literature for the last three years of 2020–2022, it is easy to find that the latest research reveals the corresponding mechanisms of action, namely through mediating and moderating variables. Ma et al [ 106 ] found that the behavior can positively affect work productivity and emotional maintenance, thus influencing employee performance, and that frequency of use and personal characteristics may moderate this process. Chen et al [ 107 ] found that using internal or external social media for work purposes could improve employee performance; using external social media for social purposes could also improve employee performance because of reduced fatigue, but using internal social media could lead to a decrease in performance because of distraction from work tasks.…”
Section: Discussionmentioning
confidence: 99%
“…From an analysis of the relevant literature for the last three years of 2020–2022, it is easy to find that the latest research reveals the corresponding mechanisms of action, namely through mediating and moderating variables. Ma et al [ 106 ] found that the behavior can positively affect work productivity and emotional maintenance, thus influencing employee performance, and that frequency of use and personal characteristics may moderate this process. Chen et al [ 107 ] found that using internal or external social media for work purposes could improve employee performance; using external social media for social purposes could also improve employee performance because of reduced fatigue, but using internal social media could lead to a decrease in performance because of distraction from work tasks.…”
Section: Discussionmentioning
confidence: 99%
“…With the widespread use of ESM, whether ESM usage could promote employee job performance has aroused practical and academic interest (Ma et al, 2021b). This study examined the influencing mechanism of supervisor-subordinate instrumental ties and expressive ties in ESM on employee job performance.…”
Section: Discussionmentioning
confidence: 99%
“…But the phenomenon of "building but not using ESM best" puzzles many enterprises. Therefore, whether ESM usage could promote employee job performance has aroused practical and academic interest (Ma et al, 2021b).…”
Section: Introductionmentioning
confidence: 99%
“…Grounded theory, a typical form of qualitative research, was first proposed in 1967 by Glaser and Strauss [ 11 ]. It has seen use in various fields of the social sciences [ 12 ].…”
Section: Methodsmentioning
confidence: 99%